PENINGKATAN PENGETAHUAN MELALUI PENYULUHAN KESEHATAN PENGELOLAAN OBAT "DAGUSIBU" PAUD BUNNAYA ICBB BANTUL - Monik Krisnawati; Nurul Izza F (ABDIMAS Madani, 2019)
The Bin Baz Islamic Center or ICBB Yogyakarta is an educational institution that manages education for elementary, middle and high school levels, while also managing early childhood education (PAUD) or Playgroup (KB). Health knowledge, especially good drug management, is not yet owned by PAUD Bunnaya ICBB students’ parents. GEMA CERMAT which stands for the movement of intelligent people using drugs is a flagship program from the Ministry of Health since 2015. The aim of the program is to increase public understanding and awareness of the importance of using drugs correctly, increasing community independence in choosing, obtaining, using, storing and destroying drugs appropriately and correctly (Ind=DAGUSIBU), as well as increasing drug use rationally. Community service is intended to provide good knowledge and management methods for the parents of students in PAUD Bunnaya ICBB. The approaches for the activities were through lecture methods and directed discussion forums. Technical implementation is conducted at one time, namely on August 15, 2018. The activities increased knowledge of the participants in managing drugs or medicines at home. In the process of activities, the participants were very active in the discussion and question and answer process.